Approach to the construction of the subject and resignigication of the body from the trascendental anthropology (Quaestiones Disputatae: temas en debate, 2021)
The integral development of the individual in the promotion of de subject being from the inherent dimensions of his human nature, is based on the knowledge that he reaches in the measure that he becomes aware of himself as a being installed in his history. In this way, he discovers himself as a being called to transcendence open to personal encounter with God. This encounter constitutes the essential source of the meaning of singular and concrete existence, which is communicated through their corporeality as the experience of his bodily being and image of God, in the participation of the construction of a web of inter-subjective relationships, which enable their own development and maturation, while contributing to the recognition of the other as a fellow man. From this perspective, the anthropological proposal of Rahner makes possible the orienting guidelines that lead to the realization of this process of self-knowledge, as an enriching source of the existential sense of each one and the resignification of corpoeality as the expression of the undestandig that each subject achieves of himself, faithful to his own nature in order to his material and spiritual vocation in the construction of a human society.
Keywords: subject; corporeality; anthropology transcendental; self-knowledge; subjectivity